Cryogenic coherent x-ray diffraction imaging for biological non-crystalline particles using the KOTOBUKI-1 diffraction apparatus at SACLA. (29th July 2015) - Oroguchi, Tomotaka; Sekiguchi, Yuki; Kobayashi, Amane; Masaki, Yu; Fukuda, Asahi; Hashimoto, Saki; Nakasako, Masayoshi; Ichikawa, Yuichi; Kurumizaka, Hitoshi; Shimizu, Mitsuhiro; Inui, Yayoi; Matsunaga, Sachihiro; et al.
Abstract: We have developed an experimental apparatus named KOTOBUKI-1 for use in the coherent x-ray diffraction imaging experiments of frozen-hydrated non-crystalline particles at cryogenic temperature. The apparatus allows us to collect diffraction data for frozen-hydrated specimens at 66 K and provides an experimental environment to easily transfer frozen-hydrated specimens from liquid nitrogen storage to the specimen stage for x-ray exposure. Since 2012, the apparatus has been used in the single-shot diffraction data collection of non-crystalline biological cells and cellular components with dimensions from micrometer to submicrometer using x-ray free electron lasers at SACLA. Here we report on the performance of the KOTOBUKI-1 diffraction apparatus and some structure analyses of biological cells and cellular components. Based on the present results, we also discuss the future developments of diffraction apparatus for more efficient data collection.